2020
DOI: 10.1101/2020.07.23.218347
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Huntingtin lowering reduces somatic instability at CAG-expanded loci

Abstract: Expanded trinucleotide repeats cause many human diseases, including Huntington’s disease (HD). Recent studies indicate that somatic instability of these repeats contributes to pathogenesis in several expansion disorders. We find that lowering huntingtin protein (HTT) levels reduces somatic instability of both the Htt and Atxn2 CAG tracts in knockin mouse models, and the HTT CAG tract in human iPSC-derived neurons, revealing an unexpected role for HTT in regulating somatic instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…We found that di-siRNA-mediated modulation of HTT had no effect on somatic repeat expansion in vivo . This finding contradicts an early preprint study in which antisense oligonucleotide (ASO)-mediated silencing of Htt reduced somatic repeat expansion ( 41 ). It is likely that the Htt -targeting ASOs reduce somatic repeat expansion by interfering with locus transcriptional rates through binding nascent nuclear targets.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…We found that di-siRNA-mediated modulation of HTT had no effect on somatic repeat expansion in vivo . This finding contradicts an early preprint study in which antisense oligonucleotide (ASO)-mediated silencing of Htt reduced somatic repeat expansion ( 41 ). It is likely that the Htt -targeting ASOs reduce somatic repeat expansion by interfering with locus transcriptional rates through binding nascent nuclear targets.…”
Section: Discussioncontrasting
confidence: 80%
“…Near complete silencing of Htt with di-valent siHTT_10150 had no measurable impact on somatic repeat expansion (instability index = 8.4±0.5) (Fig. 2H), contrasting previous HTT-lowering ASO results in this mouse model ( 41 ).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…One implication of these observations is that factors that hasten or attenuate CAG-repeat instability may also be expected to affect disease onset. It is noteworthy that a recent study has suggested a role for huntingtin protein levels in promoting CAG repeat expansion in knock-in mouse models of HD and spinocerebellar ataxia type 2, as well as in HD patient iPS-derived medium spiny neurons, although the pathways underlying these effects are yet to be delineated [157].…”
Section: Role Of Mismatch Repair In Huntington's Diseasementioning
confidence: 99%
“…This suggests huntingtin activity in DNA repair and dysfunction of mutant huntingtin may be contributing to the somatic expansion of its own gene. Indeed, one intriguing study indicates the CAG expansion in another CAG repeat disease gene, spinocerebellar ataxia type 2 (SCA2), can be affected by huntingtin levels [29].…”
Section: The Chemistry Of N6ffa Dna Adducts and The Importance Of Fan1 In Hdmentioning
confidence: 99%